The Modelling of ICT Literacy, Work Engagement, and Personal Knowledge Management to Enhance Teacher Creativity - Lisa Chandrasari Desianti; Soewarto Hardhienata; Sri Setyaningsih (Cita Konsultindo Research Center, 2023)
This quantitative research is a continuation of the qualitative research conducted on 205 private high school teachers on how teacher creativity can be influenced and enhanced. The purpose of this quantitative research is to build a model and prove whether ICT literacy, work engagement, and personal knowledge management can influence directly or indirectly increasing teacher creativity. The sampling technique uses a proportional random sampling method and determines the amount of sample based on the Taro Yamane formula. The data was collected using a questionnaire by distributing instruments to teachers in 20 private high school schools in Bogor city with data analysis techniques using Partial Least Square–Structural Equation Modeling (PLS–SEM) with the help using SmartPLS 3.0 software. The results of this study indicate that: (1) the whole variable exogenous ICT literacy, work engagement, and personal knowledge management has a positive effect on teacher creativity, either directly or indirectly; (2) work engagement and personal knowledge management have a significant effect on teacher creativity, while ICT literacy will have a significant effect on teacher creativity if through the intervening variables work engagement and/or through personal knowledge management; (3) ICT literacy has a direct and significant positive effect on work engagement and personal knowledge management; (4) the intervening variables of personal knowledge management and work engagement are proven to be able to play a full mediation role in increasing the influence of ICT literacy on creativity.